Implementation Of Earthquake Safety Bed Authenticated by GPS (International Journal of Scientific Research in Science and Technology, 2025)
An innovative earthquake safety bed system integrated with GPS technology to enhance personal safety during seismic events. The proposed system utilizes real- time earthquake detection through seismic sensors, triggered an automated response that activates safety mechanisms within the bed. GPS technology is incorporated to track the bed`s location, ensuring precise data for rescue operations and post-events analysis. System aims to minimizes injuries by providing protection features such as automatic shielding, securing the user in place, and activating emergency alerts to near by responders. By combining seismic sensing with GPS based location tracking, the earthquake safety bed offers a proactive solution to reduce harm during earthquakes, offering both immediate protection and aiding post events recovery efforts.
Keywords: GPS authentication; emergency response system; protection shields; microcontroller ATmega328p; piezo sensor; safety protection